STRATEGI PAKEM DAN TEOLOGI PELAYANAN ANAK TERHADAP PEMBENTUKAN PERILAKU ANAK YAYASAN RUMAH BELAJAR BABA - Jhonnedy Kolang Simatupang (Voice of Wesley: Jurnal Ilmiah Musik dan Agama, 2022)
To achieve a child's hope of good behavior and positive behavior requires a great deal of learning and theological study strategies for good children in an educational, family, and church environment. In the context of education, the results of failure to choose learning strategies and how to treat students are one and several things that cause children or students to have bad behavior. Therefore the purpose of this study is to know how PAKEM strategies and child service theology affect the forming of children's behavior or “Rumah Belajar Baba” participants. The research population is all over the students of the 1-6 elementary class of the baba home study foundation, which is 42 students. Through the tool of analysis used, there was an acre value. RSquare by 0.955 = 95.5%, which means X1 and X2 variables have a significant and strong relationship with the Y1 variable. The results of the hypothetical test with the statisrics effect X1 on Y1 have a value of 2,386 and P. values 0.000 , and the X2 impact on Y1 has a value of 4,706 and P.values 0.000, which suggests that the hypotheses are accepted, which means that the pakem and theological services of children have a significant impact on establishing the behaviour of “Rumah Belajar Baba” students of 1-6 class.